Pola Perkembangan Kerjaya Pelajar Menurut Perspektif Teori Super (Jurnal Pembangunan Sosial, 2010)
Not all students have been influenced by their parents background in choosing their career. The aim of this study is to examine patterns of career development for school students based on Super Career Development Theory. Descriptive research design based on cases and document analysis has been used in this study. Research participants were selected through purposive sampling and data were collected through interviews and document analysis. Results show that there are four themes identified based on Super Career Development Theory, namely students do not depend on the work of parents in determining their career, mental ability is not an important element in shaping the career self concept, the personality characteristics possessed by students influenced the way they perceive about their careers, and the pattern of career development is based on employment opportunities that existed. As a whole, this study may contribute to the development of the Super Career Development Theory.